Examining the Model for Enhancing E-Loyalty in Digital Banks - Mahfuzh, Muhammad Ady; Setyono, Joko; Riza, Alex Fahrur (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This research novelty lies in applying the Stimulus-Organism-Response (S-O-R) theory to measure e-loyalty among digital banking customers in Indonesia. This approach has not been widely explored in Indonesia's digital banks' context.Research Objectives: This research evaluates e-loyalty among digital banks' customers in Indonesia using the SOR theory's direct and indirect measurement methodologies.Research Methods: The sample consists of 130 participants drawn from customers of both Islamic and conventional digital banks in Indonesia. This research applies PLS-SEM through SmartPLS software for structural model analysis.Empirical Result: The results show that e-CRM, e-trust, and e-satisfaction directly enhance e-loyalty. E-CRM and e-trust also influence e-loyalty indirectly through e-satisfaction. Moreover, e-satisfaction mediates these relationships, highlighting its crucial role in strengthening customer loyalty in Islamic and conventional digital banks.Implications: Digital banks need to enhance e-CRM by improving application features and usability to maintain customer interaction. Additionally, e-trust is crucial to continuously strengthening security systems to reduce customer concerns. Moreover, services must consistently meet or even exceed customer expectations to achieve high satisfaction and foster customer loyalty.JEL Classification: G21, M31, D91How to Cite:Mahfuzh, M. A., Setyono, J., & Riza., A. F. (2025). Examining the Model for Enhancing E-Loyalty in Digital Banks. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 247-264. https://doi.org/10.15408/sjie.v14i1.44901.